Soil biogeochemical patterns in the Talamanca foothills, Costa Rica: local soil knowledge and implications for agroecosystems - Winowiecki, Leigh (CATIE, Turrialba (Costa Rica) | University of Idaho, Moscow, ID (EUA), 2014)
Tesis (Ph.D.) - CATIE, Turrialba (Costa Rica), 2008 Tesis (Ph.D.) - University of Idaho (Estados Unidos de América), 2008